2020
DOI: 10.1590/2447-536x.v26i1.2092
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological responses of Billbergia zebrina Lindl. (Bromeliaceae) in function of types and concentrations of carbohydrates during conventional in vitro culture

Abstract: When propagated in vitro, explants receive all the nutrients needed for their growth, including carbohydrates, from the culture medium. However, it is not well understood how the type and concentration of carbohydrates can affect the functioning of the photosynthetic apparatus (particularly photosystem II) of these plants. The aim was to assess the morphophysiological responses of Billbergia zebrina plants in function of sources and concentrations of carbohydrates during in vitro culture. Side shoots of plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Embryo rescue is one of the most feasible techniques for propagation of species with propagation limitations, mainly due to seed dormancy, such as strelitzia (Strelitzia reginae Banks ex Aiton). For plants that exhibit chemical and physical dormancy of seeds, which affects germination rates (Gomes et al, 2003;Santos et al, 2003;Paiva et al, 2004;Martins et al, 2020, Santos et al, 2020, a zygotic embryo culture can be an effective method for plant propagation (Paiva et al, 2004;Paiva;Almeida, 2012). However, although germination was observed in tests conducted in vitro, there was no multiplication or formation of somatic embryos (Paiva et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Embryo rescue is one of the most feasible techniques for propagation of species with propagation limitations, mainly due to seed dormancy, such as strelitzia (Strelitzia reginae Banks ex Aiton). For plants that exhibit chemical and physical dormancy of seeds, which affects germination rates (Gomes et al, 2003;Santos et al, 2003;Paiva et al, 2004;Martins et al, 2020, Santos et al, 2020, a zygotic embryo culture can be an effective method for plant propagation (Paiva et al, 2004;Paiva;Almeida, 2012). However, although germination was observed in tests conducted in vitro, there was no multiplication or formation of somatic embryos (Paiva et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhang et al (2018), an increased value of V K can be considered a speci c marker of damage to the activity of the OEC from the electron donor side of PSII. In turn, alterations of the values of V J and V I indicate the functioning of electron transport between the quinones (Q A and Q B ) on the receptor side of PSII and changes in the e ciency/probability of movement of electrons between the photosystems, respectively (Santos et al 2020;Martins et al 2021). In this study, we observed that the presence of Si was associated with better electron transfer between the quinones and between PSII and PSI.…”
Section: Discussionmentioning
confidence: 48%
“…In this study, the rst stress-regulation mechanisms were related to the investment in the number of stomata (stomatal density and stomatal index) in the function of Cd concentrations. These adjustments in anatomy were re ected in a decrease of the transpiration rate and mass ow, diminishing the uptake and translocation of mineral elements present in the soil or culture medium to the aerial part (Pereira et al 2017;Martins et al 2020; Pires-Lira et al 2020). These alterations were in line with the number of vessel elements (xylem).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the K-band, which occurred around 300 μs, indicates the inactivation of OEC and/or increased antenna size of PSII (Yusuf et al, 2010). The pronounced K-band can be explained by energetic imbalance between the electron donor and acceptor sides in PSII, where the electron flow from OEC to P 680 on the donor side of PSII is slower than the electron flow from PSII to Q A on the acceptor side (Yusuf et al, 2010;Santos et al, 2020). In this study, the increases observed in the K-band in both species can be attributed to the inactivation of the OEC, considering that the water stress caused the appearance of positive bands starting from WD-30.…”
Section: Discussionmentioning
confidence: 99%